PENGEMBANGAN LKPD IPA BERBASIS KOOPERATIF GROUP INVESTIGATION PADA MATERI WUJUD ZAT DAN PERUBAHANNYA UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS IV SEKOLAH DASAR - Widia Lestari, Surya; Widi Winarni, Endang; Muktadir, Abdul (UNIB Press, 2025)
The purpose of this study is to develop science student worksheets (LKPD) based on the cooperative Group Investigation model on the topic of states of matter and their changes in order to enhance students’ cognitive learning outcomes. This study employed a Research and Development (R&D) approach using the ADDIE development model. The data used in this study comprised both quantitative and qualitative data. Quantitative data were obtained through rating scale questionnaires completed by expert validators, while qualitative data were gathered from the validators' comments and suggestions. The research results indicate that the characteristics of the science LKPD based on the cooperative Group Investigation model include the core elements of the model, namely grouping, planning, investigation, organizing, presenting, and evaluation. The feasibility of the LKPD was determined through expert validation, with the material expert assigning a score of 1.00, the language expert a score of 0.94, and the design expert a score of 0.91. Student responses indicated a high level of user satisfaction, with a percentage of 96%. The average pretest score was 64.04, while the posttest average increased to 90.04. The N-Gain test for cognitive learning outcomes showed a score of 0.722, which falls into the high category.